PELAKSANAAN PENGABDIAN KEPADA MASYARAKAT MELALUI SINERGI DENGAN PADMA RESORT UBUD SEBAGAI UPAYA PENINGKATAN KOMPETENSI SDM - I Gusti Ayu Vina Widiadnya Putri; Ni Kadek Adelia Ega Pratiwi (Fakultas Bahasa Asing, 2026)
The tourism industry plays a significant role in Indonesia's economic growth, with the hospitality sector serving as one of its main pillars. Although Padma Resort Ubud has established high service standards, the hotel still faces challenges in maintaining consistent hospitality values and staff competence in handling guest complaints professionally and empathetically. This community service activity aims to improve service quality through training based on the Service Quality Theory (Parasuraman, Zeithaml, & Berry, 1985) and Emotional Labor (Hochschild, 1983). The method used is a descriptive qualitative approach with a case study design, involving participatory observation and semi-structured interviews. The results show a significant improvement in staff ability to apply active listening skills, empathetic communication, and emotional management during service interactions. Furthermore, regular briefings and continuous evaluation have proven effective in maintaining service consistency and fostering a more professional work culture. This activity demonstrates that strengthening the dimensions of empathy, responsiveness, and the practice of emotional labor can significantly enhance service quality in the hospitality sector.